Methodological issues in risk assessment of human exposure to artificial sweeteners in food - Cullen, Muireann Gearóidín (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2001)
The primary aim of this thesis is in estimating food chemical intakes with a specific interest in the area of intense sweeteners. To date all studies of intense sweeteners have been extremely detailed both in the estimate of the presence or absence of the target sweetener in each food and the level of sweetener used. Brand level data are required for definitive identification of the presence or absence of a sweetener. The Dietary and Nutritional Survey of British Adults food intake data are recorded at brand - level. This provides a unique opportunity to examine this issue of the incremental value, or otherwise, of recording brand - level food intake data. The first hypothesis of this thesis was that the retention of brand level data in food consumption databases is essential for accurate assessment of human exposure to food - borne chemicals. The precise number of subjects required reliably to establish food intake at the 97.5th percentile of the distribution of intakes was taken to be 60. Of the 1,363 brands examined, only 85 had > 60 consumers. Another important finding was that the multiple of 1.3 times the food category 97.5th percentile intake provides a robust worst - case analysis. In this study it can be seen that there is limited incremental value in retaining brand - level food intake data in food consumption databases to estimate intakes of brands among consumers and food consumption databases that do not retain brand - level data are not materially disadvantaged in assessing food additive intake.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin